Postbiotics: Functional Food Materials and Therapeutic Agents for Cancer, Diabetes, and Inflammatory Diseases - Sangiliyandi Gurunathan; Pratheep Thangaraj; Jin-Hoi Kim (Foods, 2023)
Postbiotics are (i) “soluble factors secreted by live bacteria, or released after bacterial lysis, such as enzymes, peptides, teichoic acids, peptidoglycan-derived muropeptides, polysaccharides, cell-surface proteins and organic acids”; (ii) “non-viable metabolites produced by microorganisms that exert biological effects on the hosts”; and (iii) “compounds produced by microorganisms, released from food components or microbial constituents, including non-viable cells that, when administered in adequate amounts, promote health and wellbeing”. A probiotic- and prebiotic-rich diet ensures an adequate supply of these vital nutrients. During the anaerobic fermentation of organic nutrients, such as prebiotics, postbiotics act as a benevolent bioactive molecule matrix. Postbiotics can be used as functional components in the food industry by offering a number of advantages, such as being added to foods that are harmful to probiotic survival. Postbiotic supplements have grown in popularity in the food, cosmetic, and healthcare industries because of their numerous health advantages. Their classification depends on various factors, including the type of microorganism, structural composition, and physiological functions. This review offers a succinct introduction to postbiotics while discussing their salient features and classification, production, purification, characterization, biological functions, and applications in the food industry. Furthermore, their therapeutic mechanisms as antibacterial, antiviral, antioxidant, anticancer, anti-diabetic, and anti-inflammatory agents are elucidated.